Japanese Language Learning Application Based On Android - Suryani, Ade Irma (Jurusan Informatika Universitas Tanjungpura, 2021)
The development of the world of education at this time cannot be separated from the development of science and technology, so that many learning methods have emerged in the form of applications. Lack of student interest in learning Japanese, underlies the application of Japanese language learning. The purpose of this research is that students are given information in written form or Japanese characters and vocabulary in Japanese learning applications, so that students' interest in taking Japanese language learning will increase. The method used in this research is SDLC (System Development Life Cycle) with the Waterfall model. The Waterfall model provides a sequential or sequential approach to the software life flow starting from the analysis, design, coding, testing and support stages. The result of this research is to build an Android-based Japanese learning application, which explains specifically about Japanese basic words, such as nouns, adjectives, verbs, sentences and quizzes.Keywords: The aplication, Kana (hiragana and katakana) and Android